Digital agriculture informational resources in local and international databases - M. S. Bunin; I. A. Kolenchenko; L. N. Pirumova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The article reviews informational resources on precision and digital agriculture in international cross-disciplinal and sectoral international and local databases. The databases Web of Science, Scopus, AGRIS (by FAO UN) and Engineering infrastructure of Agriculture, Rosinformagrotech, AGROS (by Central Scientific Agricultural Library) with the retrieval requests “Digital agriculture”, “Precision Agriculture” were analyzed. The authors estimated the dynamics of document flows to the AGROS database and confirmed strong growth of volume of local publications on precision agriculture to the level demonstrating technology adoption of precision agriculture. Meanwhile the level of document flow on digital agriculture is at the starting level. Analysis of most frequent publications on the topic showed that there’s no local specialized journals on precision agriculture, most frequently publications appeared in local journals such as “Machinery and equipment for rural areas”, “Soil science and agrochemistry”, “Agricultural machinery and technology”. Predominantly materials were published in specialized foreign journals “Computers and electronics in agriculture” and “Precision agriculture”. Most of the documents were obtained from WOS and Scopus databases, but a lot of them are irrelevant. While searching for foreign documents it makes sense to use all the databases available, but most of the full-size texts in open access are available in the AGRIS database. In the same way AGROS database provide a wide range of full-size texts in the Russian language. Both AGROS and AGRIS databases showed high efficiency of search with most relevant documents in search results since both databases use thesaurus as a linguistic tool.